Asthma in the older adult. (3rd March 2020) - Nanda, Anil; Baptist, Alan P.; Divekar, Rohit; Parikh, Neil; Seggev, Joram S.; Yusin, Joseph S.; Nyenhuis, Sharmilee M.
Abstract: Objective: The older adult population is increasing worldwide, and a significant percentage has asthma. This review will discuss the challenges to diagnosis and management of asthma in older adults. Data Sources : PubMed was searched for multiple terms in various combinations, including asthma, older adult, elderly, comorbid conditions, asthma diagnosis, asthma treatment, biologics and medication side effects, and adverse events. From the search, the data sources that were utilized included peer reviewed scholarly review articles, peer reviewed scientific research articles, and peer reviewed book chapters. Study Selections : Study selections that were utilized included peer reviewed scholarly review articles, peer reviewed scientific research articles, and peer reviewed book chapters. Results : Asthma in older adults is frequently underdiagnosed and has higher morbidity and mortality rates compared to their younger counterparts. A detailed history and physical examination as well as judicious testing are essential to establish the asthma diagnosis and exclude alternative ones. Medical comorbidities, such as cardiovascular disease, cognitive impairment, depression, arthritis, gastroesophageal reflux disease (GERD), rhinitis, and sinusitis are common in this population and should also be assessed and treated. Non-pharmacologic management, including asthma education on inhaler technique and self-monitoring, is vital. Pharmacologic management includes standard asthma therapies such as inhaled corticosteroids (ICS), inhaled corticosteroid-long acting β-agonist combinations (ICS-LABA), leukotriene antagonists, long acting muscarinic antagonists (LAMA), and short acting bronchodilators (SABA). Newly approved biologic agents may also be utilized. Older adults are more vulnerable to polypharmacy and medication adverse events, and this should be taken into account when selecting the appropriate asthma treatment. Conclusions : The diagnosis and management of asthma in older adults has certain challenges, but if the clinician is aware of them, the morbidity and mortality of this condition can be improved in this growing population.